(untitled) (Indian Journal of Animal Production and Management, 2017)
The study was conducted to evaluate production traits using records of 462 Sahiwal cows, spread over a period of 15 years (1997-2011), maintained at Livestock Research Centre, National Dairy Research Institute, Karnal. Data was analyzed by least squares technique to examine the effect of non-genetic factors on various economic traits in zebu cattle. Overall least squares means of total milk yield (TMY), milk yield per day lactation length (MY/LL), milk yield per day calving interval (MY/CI) were 1760.62±32.96 kg, 6.34±0.74 kg and 4.40±0.83 kg, respectively. Effect of season of calving was significant (P<0.01) on MY/LL. Period of calving and lactation order had significant (P<0.01) influence on all three production parameters, i.e. TMY, MY/LL and MY/CI. Animals of first period of calving (1997-1999) excelled in milk production performance than those of other periods. Productive performances of pluriparous animals were found better than primiparous cows. The results of this study revealed that most of milk production traits in zebu cattle were significantly affected by environmental factors. Therefore, management is an important criterion to improve environmental condition, which will ultimately improve both productive and reproductive performances in Sahiwal cows.